Comparing Students’ Procedural Text Comprehension in Experimental and Control Classes - Indriyani HF; Agus Budiyono; Arinal Husna; Yusmiati Yusmiati (Journal of English Language and Education, 2026)
Reading comprehension of procedural texts is important in English learning, but students often face difficulties due to low engagement and less interactive teaching methods. This study aimed to examine the difference in procedural text reading comprehension between students taught using Bingo Game and conventional methods. A quasi-experimental design with unequal control groups was used involving 70 tenth-grade students divided into experimental and control groups. Data were collected through pretests and posttests and analyzed using the Independent Samples t-test. The results showed that the experimental group achieved a higher mean posttest score (92.0) than the control group (80.6), with a significant difference (p 0.05). It can be concluded that Bingo Game was effective in improving students’ comprehension of procedural texts. Therefore, Bingo Game can be used as an alternative teaching strategy to create more interactive and meaningful reading instruction.